The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1136/bmj.f794
|View full text |Cite
|
Sign up to set email alerts
|

Risk of narcolepsy in children and young people receiving AS03 adjuvanted pandemic A/H1N1 2009 influenza vaccine: retrospective analysis

Abstract: Setting Sleep centres and paediatric neurology centres in England.Participants Children and young people aged 4-18 with onset of narcolepsy from January 2008. Main outcome measuresThe odds of vaccination in those with narcolepsy compared with the age matched English population after adjustment for clinical conditions that were indications for vaccination. The incidence of narcolepsy within six months of vaccination compared with the incidence outside this period measured with the self controlled cases series m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
146
2
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(171 citation statements)
references
References 17 publications
14
146
2
9
Order By: Relevance
“…Supporting the association, Miller et al [10] found a significantly increased risk of narcolepsy in children who received the vaccine in England, consistent with the findings of the cohort study conducted in Finland. It has been estimated that globally more than 1000 children have developed narcolepsy following the vaccination [12].…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Supporting the association, Miller et al [10] found a significantly increased risk of narcolepsy in children who received the vaccine in England, consistent with the findings of the cohort study conducted in Finland. It has been estimated that globally more than 1000 children have developed narcolepsy following the vaccination [12].…”
Section: Introductionsupporting
confidence: 61%
“…Following these concerns, a cohort study was conducted in Finland and the results showed that there was a 13-fold increased risk of narcolepsy in children aged 4-19 years old who received the vaccination compared to unvaccinated children [9]. These concerns led to further investigations about the incidence of narcolepsy in Europe before, during and after the swine flu pandemic and vaccination campaigns [4,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing efforts to develop more effective influenza vaccines have had limited success. In addition, the unexpected association of an adjuvanted 2009 H1N1 vaccine in Europe with increased risk of narcolepsy in children25, 26, 27 highlights the need to better understand the biologic mechanisms mediating vaccine responses.…”
Section: Discussionmentioning
confidence: 99%
“…CSL have fulfilled this role as the major supplier of influenza vaccine in Australia for more than 50 years. However, episodic vaccine safety concerns have the potential to suddenly interrupt vaccine supply from a particular manufacturer and highlight the importance of having multiple vaccine manufacturers in the market 1, 2…”
mentioning
confidence: 99%